2022
DOI: 10.3389/fmed.2022.1005121
|View full text |Cite
|
Sign up to set email alerts
|

Patients with inflammatory bowel disease are more hesitant about Coronavirus disease 2019 vaccination

Abstract: Despite the impact of the Coronavirus Disease 2019 (COVID-19) pandemic, vaccine hesitancy remains common in the general public and patients with Inflammatory Bowel Diseases (IBD). We sought to examine the reasons for vaccine hesitancy in patients with IBD. In this case-control study, we performed a retrospective chart review of 1,349 IBD patients and 215 non-IBD patients seen at University of Maryland Medical Center, a tertiary referral medical center, between March 2020 and October 2021. Data obtained include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Furthermore, regular clinic visits during acute flares and follow-ups correlated with higher COVID-19 vaccine uptake among IBD patients [47]. These findings underscore the significance of healthcare provider engagement and patient education in fostering vaccine acceptance.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, regular clinic visits during acute flares and follow-ups correlated with higher COVID-19 vaccine uptake among IBD patients [47]. These findings underscore the significance of healthcare provider engagement and patient education in fostering vaccine acceptance.…”
Section: Discussionmentioning
confidence: 68%
“…In line with our findings, other studies have also identified specific factors influencing COVID-19 vaccination rates in IBD patients. Female patients, those above the age of 50, and expatriates were more likely to receive COVID-19 vaccines [46,47]. Similarly, a study by Kwon et al observed higher vaccination uptake among IBD patients who were on biologics and of white or Asian race.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Da einige Patientinnen und Patienten mit CED unverändert Bedenken hinsichtlich einer Impfung gegen SARS-CoV-2 haben 99 100 , sollte eine entsprechende Aufklärung und Beratung durch den/die Behandler erfolgen.…”
Section: Leitlinie – Kapitel 5: Impfungenunclassified